Implicit Motives, Leadership, and Follower Outcomes: An Empirical Test of CEOs. (February 2013) - Delbecq, Andre; House, Robert J.; de Luque, Mary Sully; Quigley, Narda R.
We examined implicit or subconscious antecedents of CEO behavior and the effects on their direct subordinates. Specifically, we explored the relationships between (a) power, achievement, and affiliation motives and (b) charismatic, instrumental, and participative leadership behaviors. We then examined the influence of leadership types on three outcomes: follower motivation, performance, and teamwork. Based on analyses of interviews and surveys of 28 CEOs and 56 of their immediate followers (2 per CEO; members of the senior management team), the results indicate that only charismatic leadership relates positively to all three outcomes. Subconscious power motive relates negatively to charismatic and instrumental leadership; subconscious need for affiliation relates negatively to charismatic leadership; and subconscious need for achievement relates positively to instrumental and participative leadership. We conclude with a discussion of the implications and limitations of the study.